Putative genome features of relic green alga-derived nuclei in dinoflagellates and future perspectives as model organisms. Issue 1 (1st January 2020) - Nakayama, Takuro; Takahashi, Kazuya; Kamikawa, Ryoma; Iwataki, Mitsunori; Inagaki, Yuji; Tanifuji, Goro
ABSTRACT: Nucleomorphs, relic endosymbiont nuclei, have been studied as a model to elucidate the evolutionary process of integrating a eukaryotic endosymbiont into a host cell organelle. Recently, we reported two new dinoflagellates possessing nucleomorphs, and proposed them as new models in this research field based on the following findings: genome integration processes are incomplete, and the origins of the endosymbiont lineages were pinpointed. Here, we focused on the nucleomorph genome features in the two green dinoflagellates and compared them with those of the known nucleomorph genomes of cryptophytes and chlorarachniophytes. All nucleomorph genomes showed similar trends suggesting convergent evolution. However, the number of nucleomorph genes that are unrelated to housekeeping machineries in the two green dinoflagellates are greater than the numbers in cryptophytes and chlorarachniophytes, providing additional evidence that their genome reduction has not progressed much compared with those of cryptophytes and chlorarachniophytes. Finally, potential future work is discussed.